The role of metacognition in mindfulness interventions with Japanese EFL university students. (3rd July 2021) - Stringer, Thomas; Looney, Kathy
ABSTRACT: The role of metacognition in learning and academic achievement has been recognised. Outside of education, mindfulness has been shown to enhance metacognition and subsequent outcomes (e.g., in mental health). While mindfulness has been investigated in relation to enhancing outcomes in education, less consideration has been given to the role of metacognition as a mediating factor. The current study used a between-groups design to investigate (1) whether a mindfulness intervention significantly improves learning outcomes, mindfulness and metacognition in those learning English as a foreign language and (2) whether the relationship between mindfulness and learning outcomes is mediated by metacognition. Results of the current study were not significant. However, this study represents an important step in terms of investigating mechanisms of change in educational practices. Methodological considerations and avenues for further research are discussed.